Rapid Sketching of Woven Textile Behavior: The Experimental Use of Parametric Modeling and Interactive Simulation in the Weaving Process. (August 2022) - Meiklejohn, Elizabeth; Hagan, Brooks; Ko, Joy
Abstract: Woven textiles are typically designed with methods and software that demonstrate the graphical aspects of fabric but are limited in their representation of fabric behavior. The category of textiles that undergo shape changes in the finishing phase is well suited to alternate design approaches that incorporate predictive modeling. In this paper, we describe a methodology that uses parametric modeling and simulation to ideate, refine and inform physically produced woven fabrics with specific dimensional qualities, shifting the iterative work inherent to textile design into a digital space. Graphical abstract: Highlights: Design of woven textiles with shape changing behavior is aided by predictive workflow. Surface modeling as sketching of fabric forms is a rich iterative design experience. Woven fabrics closely resemble initial models and inform further refinements. Methodology streamlines prototyping process, broadens design language for wovens.